Leading by example (Harvard Business School Press, 2007)
Wondering how the most accomplished leaders from around the globe have tackled their toughest challenges? Now you can find out—with Lessons Learned. Concise and engaging, each volume in this new series offers 12-14 insightful essays by top leaders in business, the public sector, and academia on the most pressing issues they’ve faced. The contributors share surprisingly personal anecdotes and offer authoritative and practical advice drawn from their years of hard-earned experience.